1997
DOI: 10.1055/s-0038-1656023
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Recurrent Venous Thromboembolism in Patients with and without Factor V Leiden

Abstract: SummaryThromboprophylaxis with oral anticoagulants up to six months is established in patients after a first venous thromboembolic event (VTE). The risk of recurrent VTE is still considerable thereafter, and it is uncertain whether some patients might benefit from extended anticoagulation. We performed a prospective, multicenter trial (4 thrombosis centers) and evaluated in 380 patients with a first or recurrent VTE (patients with a deficiency of antithrombin, protein C, protein S or plasminogen; cancer; or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
117
0
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(131 citation statements)
references
References 37 publications
10
117
0
4
Order By: Relevance
“…In other hereditary thrombophilias, the annual incidence of recurrent venous thromboembolism seems to decline after the first years. 29 Surprisingly, Eichinger et al 30 found no increased risk of recurrent venous thromboembolic events in patients with the FVL mutation during the first 2 years after discontinuation of oral anticoagulants. In a recent study of the effect of prophylactic oral anticoagulation after a second peripheral venous thromboembolism, indefinite continuation of the therapy was superior to a 6-month treatment with respect to recurrence (2.6% versus 20.7%).…”
Section: Discussionmentioning
confidence: 99%
“…In other hereditary thrombophilias, the annual incidence of recurrent venous thromboembolism seems to decline after the first years. 29 Surprisingly, Eichinger et al 30 found no increased risk of recurrent venous thromboembolic events in patients with the FVL mutation during the first 2 years after discontinuation of oral anticoagulants. In a recent study of the effect of prophylactic oral anticoagulation after a second peripheral venous thromboembolism, indefinite continuation of the therapy was superior to a 6-month treatment with respect to recurrence (2.6% versus 20.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Such a conclusion has been drawn in some studies 16,17 but was not confirmed by other authors. 18,19 In a recent prospective study 20 in subjects with a previous first VTE event, we showed that normal D-dimer levels obtained after OAT withdrawal had a very high negative predictive value for VTE recurrence. Conversely, increased D-dimer levels were associated with a significantly higher hazard ratio for recurrence.…”
mentioning
confidence: 89%
“…The role of thrombophilic abnormalities, especially those that are highly prevalent in western countries (i.e., factor V Leiden and prothrombin G20210A mutation), is controversial. [5][6][7][8][9][10][11][12][13][14] Although recent data suggest that clinical presentation with primary PE 15 and male sex [16][17][18] increase the risk of recurrent VTE, these findings still await confirmation. Finally, whether the duration of anticoagulation following the initial thrombotic episode has any influence on the subsequent rate of recurrent VTE is uncertain.…”
mentioning
confidence: 99%